2014
DOI: 10.1002/smi.2589
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Positive Emotions, Coping, Resilience and Mental Health

Abstract: The broaden-and-build theory of positive emotions suggests that positive emotions can widen the range of potential coping strategies that come to mind and subsequently enhance one's resilience against stress. Studies have shown that high stress, especially chronic levels of stress, strongly contributes to the development of anxiety and depressive symptoms. However, researchers have also found that individuals who possess high levels of resilience are protected from stress and thus report lower levels of anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
211
1
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(238 citation statements)
references
References 51 publications
9
211
1
17
Order By: Relevance
“…Rates of use of MBMB among children with EMB in the United States suggest delayed and underuse of these promising methods. 36-38 Findings support integrated, family-centered, and mindfulness-based trauma-informed approaches to address social and emotional trauma and interrupt intergenerational cycles of ACEs and their contribution to EMB among children and youth.…”
Section: Discussionmentioning
confidence: 76%
“…Rates of use of MBMB among children with EMB in the United States suggest delayed and underuse of these promising methods. 36-38 Findings support integrated, family-centered, and mindfulness-based trauma-informed approaches to address social and emotional trauma and interrupt intergenerational cycles of ACEs and their contribution to EMB among children and youth.…”
Section: Discussionmentioning
confidence: 76%
“…Some persons have genetic resilience to the development of negative consequences after trauma exposure (DiGangi et al, 2013;Carli et al, 2011). Studies have suggested that individuals may have protective factors that promote resilience against stressors (Gloria & Steinhardt, 2014). Certain factors have been associated with resilience, including personality traits such as increased cognitive ability, high self-esteem, and an internal locus, as well as social support (McElroy & Hevey, 2013).…”
Section: Resiliencementioning
confidence: 98%
“…One explanation of why some employees focused on the benefits of stressors within open-plan offices was that they had the skills to work through the negative aspects of stressors (Gloria & Steinhardt, 2016). However, this study's findings were different to Rasila & Jylhä's (2014) study because they studied open-plan office noise, an environmental stressor in general.…”
Section: Perspectives Of Anxiety: the Dark Side And Bright Sidementioning
confidence: 64%
“…The open-plan office is a highly stressful working environment, which heightens employees' vulnerability to experiencing anxiety (Gloria & Steinhardt, 2016). Stress is experienced when an individual perceives that a demand threatens their wellbeing (Holroyd & Lazarus, 1982).…”
Section: The Dark Side Of Anxiety Within Open-plan Officesmentioning
confidence: 99%
See 1 more Smart Citation